2011
DOI: 10.1111/j.1834-7819.2011.01324.x
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of bacterial flora in progress of peri‐implant disease

Abstract: Background: Cumulative interceptive supportive therapy (CIST) is currently used as a guideline for treating peri-implant diseases. The objectives of this study were to determine the detection rate and measure the number of periodontopathic bacteria in lesions of different CIST levels and thereby characterize peri-implant disease from a bacteriological viewpoint. Methods: This study included 105 patients who had both residual natural teeth and implants with peri-implant disease. A total of 105 implants were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 19 publications
1
20
0
6
Order By: Relevance
“…Of these, 87 were excluded after review of the title or abstract, and 39 1,9,10,13,14,16‐19,23‐52 full‐text studies were reviewed. Ultimately, 26 studies 9,10,13,14,16‐19,27,36‐52 were included (Table 1), and 13 1,23‐30,32‐35 were excluded for different reasons (12 1,23‐30,33‐35 for not fulfilling the proposed inclusion criteria and one 32 due to its retrospective design). In total, 1,145 patients with 2,134 implants were assessed in the 26 cross‐sectional studies studies 7,9,10,13,14,16‐19,27,36‐46,48‐52 that were included in this review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 87 were excluded after review of the title or abstract, and 39 1,9,10,13,14,16‐19,23‐52 full‐text studies were reviewed. Ultimately, 26 studies 9,10,13,14,16‐19,27,36‐52 were included (Table 1), and 13 1,23‐30,32‐35 were excluded for different reasons (12 1,23‐30,33‐35 for not fulfilling the proposed inclusion criteria and one 32 due to its retrospective design). In total, 1,145 patients with 2,134 implants were assessed in the 26 cross‐sectional studies studies 7,9,10,13,14,16‐19,27,36‐46,48‐52 that were included in this review.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 87 were excluded after review of the title or abstract, and 39 1,9,10,13,14,[16][17][18][19] full-text studies were reviewed. Ultimately, 26 studies 9,10,13,14,[16][17][18][19]27,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] were included (Table 1), and 13 1,[23][24][25][26][27][28][29][30][32][33][34][35] were excluded for different reasons (12 1,23-30,33-35 for not fulfilling the proposed inclusion criteria and one 32 due to its re...…”
Section: Search Results and Excluded Trialsmentioning
confidence: 99%
“…Interestingly, Sato et al found a higher number and detection rate of periodontopathic bacteria as the cumulative interceptive supportive therapy (CIST) level increased [57]. …”
Section: Resultsmentioning
confidence: 99%
“…), end‐point and real‐time PCR (Sato et al. ; Galassi et al. ), denaturing gradient gel electrophoresis (Zijnge et al.…”
Section: Discussionmentioning
confidence: 99%
“…These species have also been implicated as putative pathogens in the pathogenesis of periodontitis (Slots et al 1988;Rams et al 1990Rams et al , 1992Socransky et al 1998). Additional bacterial species and novel phylotypes may be identified in peri-implantitis lesions with other types of selective culture media (Rams et al 1990(Rams et al , 1992 and with various nucleic acid-based molecular methods, such as checkerboard DNA-DNA hybridization (Leonhardt et al 2003a), end-point and real-time PCR (Sato et al 2011;Galassi et al 2012), denaturing gradient gel electrophoresis (Zijnge et al 2006;Al-Radha et al 2012), and 16S ribosomal RNA sequencing (Koyanagi et al 2010;Kumar et al 2012). It is not known from the present retrospective study design whether these organisms initiated periimplantitis similar to periodontitis, or merely colonized deep peri-implant probing depths secondarily after other etiologic factors triggered the onset of peri-implant marginal tissue breakdown.…”
Section: Discussionmentioning
confidence: 99%